2018
DOI: 10.1136/jclinpath-2018-205292
|View full text |Cite
|
Sign up to set email alerts
|

Claudin-1 is linked to presence of implants and micropapillary pattern in serous borderline epithelial tumours of the ovary

Abstract: In conclusion, Claudin-1 expression is associated with the presence of peritoneal implants and micropapillary pattern, which have been shown to be associated with poor prognosis. We speculate that overexpression of Claudin-1 might be linked to the mitogen-activated protein kinase pathway activation in BOT and suggest further studies to define its prognostic and potential therapeutic value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Extensive studies conducted and analyzed for the association of CLDN-1 with survival and anatomical site showed 85% elevation of CLDN-1 expression [58]. Recently, the level of CLDN-1 expression was also investigated in borderline tumors of the ovary (BOT) [53]. A significantly higher level of CLDN-1 expression was associated with the peritoneal implants and micropapillary patterns that are specifically seen only in serous BOT [53].…”
Section: Claudin-1 and Ovarian Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive studies conducted and analyzed for the association of CLDN-1 with survival and anatomical site showed 85% elevation of CLDN-1 expression [58]. Recently, the level of CLDN-1 expression was also investigated in borderline tumors of the ovary (BOT) [53]. A significantly higher level of CLDN-1 expression was associated with the peritoneal implants and micropapillary patterns that are specifically seen only in serous BOT [53].…”
Section: Claudin-1 and Ovarian Cancermentioning
confidence: 99%
“…Recently, the level of CLDN-1 expression was also investigated in borderline tumors of the ovary (BOT) [53]. A significantly higher level of CLDN-1 expression was associated with the peritoneal implants and micropapillary patterns that are specifically seen only in serous BOT [53].…”
Section: Claudin-1 and Ovarian Cancermentioning
confidence: 99%
“…62 In addition, El-Balat et al found that Claudin-1 is related to predictors of poor prognosis (eg, peritoneal implantation and micropapillary pattern), and the authors hypothesized that the overexpression of Claudin-1 may be related to the activation of the mitogen-activated protein kinase (MAPK) signaling pathway. 63 Different from inhibited p53 signaling in high-grade serous ovarian cancer (HGSOC), overexpressed p53 and changes in genes associated with the p53 pathway were observed in SBOTs. 64 Cheng et al 65 confirmed that SBOTs contained wild-type p53 by sequencing.…”
Section: Gene Expression and Pathways Alteration In Botsmentioning
confidence: 99%
“…Recent studies have inferred several assumptions, including the incessant ovulation, gonadotropin, hormonal, and inflammation hypotheses, to explain the tumorigenesis of serous BOTs [ 17 , 18 , 19 ]. Serous BOTs are characterized by mutations in the KRAS , BRAF , and ERBB2 genes and overexpression of the p53 and Claudin-1 genes; furthermore, the mitogen-activated protein kinase (MAPK)/extracellular signal-regulated kinase (ERK) pathway, PI3K/AKT/mTOR pathway, Hedgehog pathway, and angiogenesis pathway are frequently activated in serous BOTs [ 13 , 14 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%